Discover a wealth of knowledge at Westonci.ca, where experts provide answers to your most pressing questions. Discover a wealth of knowledge from experts across different disciplines on our comprehensive Q&A platform. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.

Solve for X and Y 1. y = 2x
6x + 3y = 12

2. y = -4x + 2
y = 6x - 8

3. y = x - 4
-4x - 6y = -16

4. x = 3y + 1
2x + 4y = 12


Sagot :

Answer:

Step-by-step explanation:

1.  If y =2x

solve for y in (6x +3y) = 12

6x + 3(2x) = 12,   6x + 6x =12

12x = 12 ,  x= 1

to find y ,   from y =2x

y = 2(1)  , ( x = 1 and y = 2)

2.  y = -4x + 2

    y = 6x -8

y = (-4x + 2)(6x-8)

= -4x ( 6x -8) + 2(6x-8)

-24[tex]x^{2}[/tex] + 32x + 2(6x-8)

-24x2 + 44x - 16

3.  y = x -4

  -4x -6y = -16

  -4x - 6(x - 4) = -16

 -4x - 6x - 24 = -16

-10x - 24 = -16

-10x = -16 + 24,   -10x = -8

x = 0.8 , to get y , we input x value into eqn(y = x-4)

y = 0.8 -4,   y = -3.2

x = 0.8,   y = -3.2.

4.  x = 3y + 1

 2x + 4y =12

2(3y + 1)  + 4y = 12

6y + 2 + 4y = 12

10y + 2 = 12

10y = 12 -2

10y = 10

y = 1,  to get x

x = 3y + 1

x = 3(1) + 1 ,  x = 4

( x = 4 and y = 1).

Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. We're here to help at Westonci.ca. Keep visiting for the best answers to your questions.